A Lamellar Hybrid Assembled from Metal Disulfide Nanowall Arrays Anchored on a Carbon Layer: In Situ Hybridization and Improved Sodium Storage. Issue 35 (30th June 2016) - Ding, Yuan‐Li; Kopold, Peter; Hahn, Kersten; van Aken, Peter A.; Maier, Joachim; Yu, Yan
Abstract : A lamellar hybrid assembled from metal disulfide (MoS2, WS2 ) nanowall arrays anchored on nitrogen‐doped carbon layers is developed via an in situ hybridization strategy through a synergistic pyrolysis reaction of thiourea and oxometalates. Such a hybrid provides adequate electrical and chemical coupling between the active materials and the carbon substrate, thus realizing a high‐efficiency electron‐conduction/ion‐transportation system and exhibiting excellent sodium‐storage properties.